Kalkınma yolu projesi bağlamında Habur Sınır Kapısı’nın sağlık lojistiğindeki stratejik rolü - Aralan, Tuba; Demirtaş, Meryem (Dünya Kongre, 2025)
ÖZET Amaç: Çalışmanın amacı, Türkiye'nin sağlık lojistiği kapasitesini sınır geçiş altyapısı bağlamında değerlendirmek ve Habur Sınır Kapısı özelinde bu kapasitenin mevcut durumu ile geliştirme potansiyelini SWOT analizi yöntemiyle incelemektir. Özellikle Kalkınma Yolu Projesi kapsamında, sınır geçiş noktalarının sağlık lojistiği üzerindeki stratejik rolü analiz edilmiştir. Yöntem: Çalışmada, Türkiye’nin sağlık ürünleri dış ticaret verileri, taşıma modları ve sınır kapılarındaki işlem hacmi incelenmiştir. Habur Sınır Kapısı’nın mevcut altyapı kapasitesi, dijital izlenebilirlik düzeyi ve soğuk zincir sistemleri SWOT analizi yöntemiyle değerlendirilmiştir. Bulgular: Habur Sınır Kapısı, taşıma hacmi açısından güçlü bir altyapıya sahip olmakla birlikte, sağlık lojistiği açısından bazı temel yetersizlikler barındırmaktadır. Özellikle soğuk zincir altyapısının sınırlılığı, sağlık ürünlerine yönelik özel taşıma protokollerinin eksikliği ve dijital izleme sistemlerinin yetersizliği, mevcut kapasitenin verimli kullanımını sınırlamaktadır. Sonuç: Kalkınma Yolu Projesi kapsamında planlanan lojistik merkezler ve dijital altyapı yatırımları, bu yapısal eksiklikleri giderme potansiyeli taşımaktadır. Ayrıca, tıbbi ürün taşımacılığına özel hatlarla desteklenecek lojistik köylerin kurulması durumunda, sınır bölgelerindeki sağlık sistemlerinin krizlere müdahale kapasitesinin artırılabileceği öngörülmektedir. Genel olarak çalışma, sağlık lojistiğinin yalnızca ulaştırma politikaları bağlamında değil, bölgesel kalkınma ve sağlık sistemlerinin dayanıklılığı çerçevesinde ele alınması gerektiğini vurgulamaktadır. Anahtar Kelimeler: Sağlık Lojistiği, Habur Sınır Kapısı, Kalkınma Yolu Projesi, Soğuk zincir taşımacılığı

ABSTRACT Aim: The aim of this study is to evaluate Turkey’s health logistics capacity in the context of border crossing infrastructure and to analyze, through a SWOT methodology, the current situation and development potential of the Habur Border Gate. Specifically, the study examines the strategic role of border crossings in health logistics within the scope of the Development Road Project. Method: The research employs a multi-level analytical approach. National-level foreign trade data related to health products (pharmaceuticals and medical devices), transportation modes, and transaction volumes at border gates were examined. The operational and infrastructural capacity of the Habur Border Gate was evaluated using SWOT analysis, with a specific focus on cold chain compatibility, digital traceability systems, and health-related customs protocols. Results: Findings indicate that while Habur possesses a robust logistics throughput, its capacity for handling health-related goods remains limited. The absence of dedicated cold chain infrastructure, insufficient institutional frameworks for medical cargo handling, and underdeveloped digital monitoring systems constrain its effectiveness. These limitations highlight the gap between the border gate’s existing infrastructure and the requirements of an integrated health logistics node. Conclusion: The Development Road Project offers potential to mitigate current structural deficiencies through the establishment of multimodal logistics hubs and enhanced digital infrastructure. If complemented with dedicated lanes and facilities for medical goods, these interventions could significantly strengthen the resilience and crisis-response capabilities of regional health systems. The study underscores the importance of integrating health logistics planning not only within transport strategies but also into broader regional development and public health preparedness frameworks. Keywords: Health Logistics, Habur Border Crossing, Development Road Project, Cold Chain Transportation
The strategic role of Habur border gate in health logistics in the context of development road project
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi